2016
DOI: 10.1094/mpmi-04-16-0068-r
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous Pathogenicity Islands and Phylogeny of Pathogenic Streptomyces spp.

Abstract: Approximately 10 Streptomyces species cause disease on underground plant structures. The most economically important of these is potato scab, and the most studied of these pathogens is Streptomyces scabiei (syn. S. scabies). The main pathogenicity determinant of scab-causing Streptomyces species is a nitrated diketopiperazine, known as thaxtomin A (ThxA). In the pathogenic species Streptomyces turgidiscabies, ThxA biosynthetic genes reside on a mobile pathogenicity island (PAI). However, the mobilization of PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 56 publications
5
45
1
Order By: Relevance
“…A soft nutrient agar overlay containing antibiotics was used to select for transconjugants. In our previous study, we demonstrated the mobilization of the complete TR element or TR2 alone between S. scabiei and S. diastatochromogenes (Zhang et al ., ). PAIst was also found to excise from the chromosome in three distinct forms: as the 105‐kb region, the 569‐kb region or the entire 674‐kb PAIst (Huguet‐Tapia et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…A soft nutrient agar overlay containing antibiotics was used to select for transconjugants. In our previous study, we demonstrated the mobilization of the complete TR element or TR2 alone between S. scabiei and S. diastatochromogenes (Zhang et al ., ). PAIst was also found to excise from the chromosome in three distinct forms: as the 105‐kb region, the 569‐kb region or the entire 674‐kb PAIst (Huguet‐Tapia et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…To explore the mobilization of regions containing the ThxA biosynthetic genes, we used S. turgidiscabies Car811 with a thiostrepton resistance (thio R ) marker inserted in its PAIst (Kers et al, 2005) and a mutant strain of S. scabiei 87-22 created by replacing its lantibiotic biosynthetic genes lanA (SCAB_32021) and lanB (SCAB_32031) located in TR with the hygromycin B resistance (hyg R ) marker (hereafter referred to as S. scabiei DlanAB) (Zhang et al, 2016). A schematic genetic organization of the S. scabiei TR with the hyg R marker and the S. turgidiscabies PAIst with the thio R marker is shown in Fig.…”
Section: Mobilization Of S Scabiei Tr and S Turgidiscabies Paistmentioning
confidence: 99%
See 2 more Smart Citations
“…is regarded as an acquired trait since the pathogenicity island (PAI) harbouring the main virulence determinants is found to be mobilized from pathogenic to nonpathogenic species among streptomycetes, thereby giving rise to the newly emerged pathogenic strains (Wanner and Kirk ; Zhang et al . ). Given that S. scabies is the most ancient phytopathogenic Streptomyces sp.…”
Section: Introductionmentioning
confidence: 97%